Correlates of job performance and job satisfaction of nurse corps officers in selected military hospitals - De Vera, Ricardo P. (1999)
Continuous quality improvement of patient care is great challenge to all nurses throughout the world. It is not only the responsibility of the nurse administrators but also of the individual nurse to monitor the sustainment or improvement of the quality of patient care, but also of the individual nurse as well. Thus, monitoring of the performance and satisfaction through appraisal, counselling, and quality control activities are done to improve and maintain nursing care delivered to the clientele.This study aims to determine the relationship among selected antecedent variables to job performance and job satisfaction. Specially, the intention is to evaluate the levels of job performance and job satisfaction of military nurses, and their correlates. Assessment of job satisfaction and job performance is found to be effective in the maintenance or improvement of nursing care delivery.The conceptual framework of the study is established on the fact that independent variables, such as socio-demographic factors and work related factors may affect the performance and satisfaction of military nurses. Considered for the socio-demographic factors: age, sex, and civil status, while for the work related factors included are: position, educational attainment, salary, rank, and length of service. Corollary, on relationship between job satisfaction and job performance is considered. Descriptive correlational survey method was used in this study which was conducted in four military hospitals of the major services found in Metro Manila from June to December 199. With 77 military nurses participating in the study, the following are the findings:1. On the relationship between personality traits and performance.Personality traits that are dominant in good performing nurses are: emotionally stable, cooperative, practical, organized, imaginative, and forgiving. Traits of moderate performing nurses are: cooperative, relaxed serious, trusting, careful, sensitive, and responsible. Finally, the dominant traits of low performing nurses are: trusting and conscientious.2. On the relationship between socio-demographic factors and job performance/job satisfaction.Socio demographic variables are said to be correlated with performance and satisfaction of military nurses. Performance and age are strongly correlated, while civil status has negative moderate correlation. Sex is moderately correlated with performance.With respect to satisfaction, sex has negative strong correlation, while the age and civil status have a negative moderate correlation.3. On relationship between work related factors and nurses' job performance/satisfaction.
Work related factors are associated with nurses' performance and satisfaction. For the performance, area assignment and educational attainment have moderate correlation to job performance, while salary has a low relationship. Area assignment and educational attainment do not affect the nurses' performance. The same is true with rank and salary.4. On the level of military nurses' job performance.Metro Manila military nurses are performing very satisfactorily based on AFP performance appraisal system/standard.5. On the level of military nurses job satisfaction.Metro Manila military nurses are moderately satisfied with their present job based on the standard established in the study.6. On the relationship between job performance and job satisfaction.The outcome of the study disclosed that job performance and job satisfaction have a very weak relationship (r=.08).The above findings support the following conclusions:(1) Metro Manila military nurses perform their job very satisfactory;(2) Metro Manila military nurses are moderately satisfied with their present job;(3) Traits which produce high performance are: emotionally stable, cooperative, practical, organized, immaginative and forgiving.(4) Age, position, and length of service are strongly related to performance;(5) Area assignment, interpersonal relationship, group cohesiveness, and leadership behavioral are strongly correlated to job satisfaction;(6) Job performance and job satisfaction are not related to each other.The findings of this study can serve as the basis for the decision making and strategic planning towards the improvement of job satisfaction and performance among military nurses. However, to be highly relevant and responsive to changes, the need for future re-evaluation of this study is underscored.Nursing promotes and preserves health for everyone. For nurses to be true to their profession, they have the responsibility to provide quality care to their clientele.
Thesis (Master of Arts in Nursing)--University of the Philippines Manila.
Keywords: Military nursing; Nurses -- Job satisfaction